INSTALASI PIPA HDPE UNTUK SALURAN AIR BERSIH PADA PROYEK PEKERJAAN JALAN DI PIER - Achmad Dafa' Purwanto; Elisa Stefani Simanjuntak; Hendrata Wibisana (Racic : Rab Construction Research, 2026)
High Density Polyethylene (HDPE) pipes are widely applied in clean water distribution systems due to their flexibility, corrosion resistance, and long service life. This study discusses the installation stages of HDPE pipes in a road construction project at the PIER area, including excavation preparation, pipe installation, jointing using the butt fusion method, and hydrostatic pressure testing. The butt fusion process is carried out by controlling temperature, pressure, and heating time in accordance with technical standards to obtain homogeneous joints with strength comparable to the pipe material. Furthermore, hydrostatic pressure testing is conducted to evaluate joint tightness and to ensure the absence of leakage within the piping system. The results indicate that proper field procedures and compliance with applicable standards significantly influence joint quality and the success of pressure testing. This study is expected to serve as a technical reference for the safe and effective implementation of HDPE pipe installations that comply with quality standards.